Comparative Glycopeptide Analysis for Protein Glycosylation by Liquid Chromatography and Tandem Mass Spectrometry: Variation in Glycosylation Patterns of Site-Directed Mutagenized Glycoprotein - Young Hye Hahm; Sung Ho Hahm; Hyoun Young Jo; Yeong Hee Ahn (International Journal of Analytical Chemistry)
Glycosylation is one of the most important posttranslational modifications for proteins, including therapeutic antibodies, and greatly influences protein physiochemical properties. In this study, glycopeptide mapping of a reference and biosimilar recombinant antibodies (rAbs) was performed using liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) and an automated Glycoproteome Analyzer (GPA) algorithm. The tandem mass analyses for the reference and biosimilar samples indicate that this approach proves to be highly efficient in reproducing consistent analytical results and discovering the implications of different rAb production methods on glycosylation patterns. Furthermore, the comparative analysis of a mutagenized rAb glycoprotein proved that a single amino acid mutation in the Fc portion of the antibody molecule caused increased variations in glycosylation patterns. These variations were also detected by the mass spectrometry method efficiently. This mapping method, focusing on precise glycopeptide identification and comparison for the identified glycoforms, can be useful in differentiating aberrant glycosylation in biosimilar rAb products.